Cercyon hungaricus, a new junior subjective synonym of C. bononiensis (Coleoptera: Hydrophilidae) - Fikáček, Martin; Rocchi, Saverio (Zootaxa, 2013)
Cercyon bononiensis Chiesa, 1964 was described from two specimens collected in northern Italy in 1924–1925. For some time, these specimens were identified as C. inquinatus Wollaston, 1854. Only 40 years later, having examined the type of the latter species, Chiesa (1964) realized that the two specimens belonged to an undescribed species that he then described as Cercyon bononiensis. Based on the chagrined elytra mentioned in the original description, C. bononiensis has been placed in the Cercyon tristis group by subsequent authors. Recently, we examined a small number of Cercyon specimens from northern Italy and surprisingly found two specimens of C. hungaricus Endrödy-Younga, 1967, an easily recognizable member of the C. tristis group which was previously considered a Pannonian endemic by Fikáček et al. (2009) but was recently also found in northern Germany (Bäse 2010). The presence of this unusual species led us to question whether C. hungaricus might be conspecific with C. bononiensis. This was subsequently confirmed by the study of the types of both species. Here, we provide a summary of our studies and synonymize C. hungaricus with C. bononiensis. Examined specimens are deposited in the following collections: Hungarian Natural History Museum, Budapest, Hungary (HNHM), Museo Civico di Storia Naturale Milano, Italy (MSNM), collection of S. Rocchi at the Museo di Storia Naturale dell’Università di Firenze, Sezione di Zoologia "La Specola" (CRO).